Reimplantasi gigi avulsi Reimplantation of avulsed teeth - Fonny Dahong; Lies Wahyuni Winarso (DiscoverSys Inc., 2012)
It is well known dental reimplantation is indicated following traumatic avulsion by the preservation of vitality in theperiodontal ligament with condition asepsis. Reimplantation refers to the insertion and temporary of completely orpartially avulsed teeth that have resulted from traumatic injury. Dental reimplantation of an avulsed tooth dependson certain clinical conditions like physiological status of periodontal ligament, the stage of root development andthe length of extra oral time. Depending on the patient’s age, retention of the permanent incisor can maintain theaesthetic appearance, occlusal function and alveolar ridge height. Though the risk of progressive replacementresorption and subsequent tooth loss is high after a long dry storage. This article presents management of one casewith avulsed permanent incisors that were storage in dry condition for seventeen hours